Impressic acid from Acanthopanax koreanum, possesses matrix metalloproteinase-13 down-regulating capacity and protects cartilage destruction. (14th September 2017) - Lim, Hyun; Min, Dong Suk; Yun, Han Eul; Kim, Kil Tae; Sun, Ya Nan; Dat, Le Duc; Kim, Young Ho; Kim, Hyun Pyo
Abstract: Ethnopharmacological relevance: Acanthopanax koreanum (Araliaceae) has been used in traditional medicine for enhancing vitality, rheumatism, and bone-related pains. But its activity on cartilage protection has not been known yet. Aim of the study: Matrix metalloproteinase (MMP)−13 has an important role in degrading cartilage materials under pathologic conditions such as arthritis. The present study was designed to find the inhibitory activity of impressic acid on MMP-13 expression and cartilage protective action. Materials and methods: 70% ethanol extract of Acanthopanax koreanum leaves and impressic acid, a major constituent isolated from the same plant materials, were examined on MMP-13 down-regulating capacity in IL-1β-treated human chondrocyte cell line (SW1353) and rabbit cartilage explants. Results: In IL-1β-treated SW1353 cells, impressic acid significantly and concentration-dependently inhibited MMP-13 expression at 0.5–10 μM. Impressic acid was found to be able to inhibit MMP-13 expression by blocking the phosphorylation of signal transducer and activator of transcription-1/−2 (STAT-1/−2) and activation of c-Jun and c-Fos among the cellular signaling pathways involved. Further, impressic acid was found to inhibit the expression of MMP-13 mRNA (47.7% inhibition at 10 μM), glycosaminoglycan release (42.2% reduction at 10 μM) and proteoglycan loss in IL-1-treated rabbit cartilage explants culture. In addition, a total of 21 lupane-type triterpenoids structurally-related to impressic acid were isolated from the same plant materials and their suppressive activities against MMP-13 expression were also examined. Among these derivatives, compounds2, 3, 16, and18 clearly down-regulated MMP-13 expression. However, impressic acid was more potent than these derivatives in down-regulating MMP-13 expression. Conclusions: Impressic acid, its related triterpenoids, and A. koreanum extract have potential as therapeutic agents to prevent cartilage degradation by inhibiting matrix protein degradation. Graphical abstract: